A TINJAUAN APLIKASI E-FAKTUR UNTUK PKP ATAS PELAPORAN SPT MASA PPN - Muhtar Udin (Jurnal Komputer Bisnis, 2022)
This study aims to make it easier for Taxable Entrepreneurs to process input tax and output tax invoices so as to facilitate the reporting of Periodic Value Added Tax Returns (VAT) as a tax obligation. In this study the authors used a descriptive method with a case study approach to one of the clients at YR Tax Consultants. The data obtained from this research is by carrying out field work practices, interviewing YR Tax Consultants employees, using data or documents from March to June 2021 and gathering the necessary theories. From the results of this study it can be concluded that reporting Periodic Value Added Tax (VAT) SPT using the e-Faktur application facilitates the process, but there are several factors that hinder the reporting process such as interference with internet connections to other problems experienced by clients.